1990
DOI: 10.1063/1.102608
|View full text |Cite
|
Sign up to set email alerts
|

Lattice contraction due to carbon doping of GaAs grown by metalorganic molecular beam epitaxy

Abstract: Epitaxial layers of GaAs have been grown by metalorganic molecular beam epitaxy (MOMBE) with atomic carbon concentrations ranging from 4 X 10 17 to 3.5 X Ufo cm-I. The dependences of GaAs lattice parameter and hole concentration on atomic carbon concentration have been determined from x-ray diffraction, Hal! effect, and secondary-ion mass spectrometry measurements. For atomic carbon concentrations in excess of 1 X Wi'! cm-3, the hole concentrations are less than the corresponding atomic carbon concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…To within experimental error ͑estimated to be Ϯ20% for ͓C͔͒, these results are consistent with approximate equality of p and ͓C͔, i.e., close to full activation of C As donors. This is what is expected, and it agrees with a substantial body of reported work 1,3,8,13,47 for GaAs:C. But if our ͑Hall-derived͒ p values were too low by a factor of 2 ͑as required by r Hall ϭ2.0), this would correspond to a hole concentration that is twice the carbon concentration, which is highly implausible. We therefore conclude that r Hall cannot be 2.0, but is instead much closer to 1.0.…”
Section: Hole Mobility: Infrared Versus Hallsupporting
confidence: 77%
“…To within experimental error ͑estimated to be Ϯ20% for ͓C͔͒, these results are consistent with approximate equality of p and ͓C͔, i.e., close to full activation of C As donors. This is what is expected, and it agrees with a substantial body of reported work 1,3,8,13,47 for GaAs:C. But if our ͑Hall-derived͒ p values were too low by a factor of 2 ͑as required by r Hall ϭ2.0), this would correspond to a hole concentration that is twice the carbon concentration, which is highly implausible. We therefore conclude that r Hall cannot be 2.0, but is instead much closer to 1.0.…”
Section: Hole Mobility: Infrared Versus Hallsupporting
confidence: 77%
“…Sharp epitaxial-layer peaks, the presence of PendellSsung fringes, anda low background level are an indication of the high quality of the layers. The position of the GaAs : C (AlAs : C) peak gives information about the incorporated C concentration [2,7]. This is an essential parameter to determine the effectiveness of the carbon incorporation, since the C concentration incorporated on lattice sites CAs can be smaller than the total C concentration CT, i.e.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Carbon acts asa p-type dopant in GaAs and AlAs. At the same time, it produces a strong contraction of the lattice [2]. Therefore, we have used carbon to produce highly doped p-type DBRs, which are simultaneously strain-compensated.…”
Section: -Introduetionmentioning
confidence: 99%
“…7 Moreover, it was observed that the annealing of highly C-doped GaAs at temperatures between 600 and 850°C leads to a drastic reduction in the hole concentration ͓ p͔. [8][9][10] This cannot be explained by interstitial diffusion, but instead the formation of compensating defects is required. Below ϳ550-600°C or at low carbon concentrations, degradation was not observed: ͓p͔ increased to a level nearly equal to ͓C͔.…”
Section: Introductionmentioning
confidence: 99%